Is there any positive effect of offering no performance appraisal feedback? - Lee, Mushin; Shin, Wonjun (2000)
So far researchers have regarded performance appraisal feedback as desirable and have examined feedback issues assuming that feedback is actually provided. The purpose of this article is to investigate whether there is any positive effect of offering no performance appraisal feedback. We studied if the inflated expectation of employees' own performance appraisal affects the performance of the employee positively inflated and it made significant contributions to compliance with supervisor, job satisfaction and organizational commitment. The results also showed that expectation of their supervisors' rating is a more significant indicator than the real appraisal rating itself in reviewing some employee attitudes like compliance with supervisor and organizational commitment. Several theoretical and managerial implications of the findings, including the importance of cultural difference, were also discussed. - Reproduced
Keywords: Performance appraisal